Tourism and social clubs [videorecording]. (Quezon City : Felta Multi Media Inc.)
Explore the many types of hospitality careers available including serving food and beverages, hotel reception and front office positions, tourism, social clubs, housekeeping, kitchen employee and airline employee. A program that walks you through the responsibilities and basic skills required, both when dealing with the public behind the scenes.
Keywords: Tourism; Hospitality industry; Food service -- management; Tourism trade